Selective dsDNA-templated formation of copper nanoparticles in solution - Rotaru, Alexandru; Dutta, Subrata; Jentzsch, Elmar; Gothelf, Kurt; Mokhir, Andriy (Angewandte Chemie. International edition, 2010)
A helping strand: A method to selectively form copper nanoparticles in solution using double-stranded DNA has been developed. The size of the nanoparticles is controlled by the length of the dsDNA template, and single-stranded DNA did not act as a template (see scheme). Single-stranded overhangs in dsDNA were used to prepare a nanostructure in which two metallized dsDNA segments were linked together by a nonmetallized rigid linker.